1964
DOI: 10.3758/bf03342800
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ordinal position and sibling sex status to cognitive abilities

Abstract: The influence of the interaction of ordinal position and sibling sex status on cognitive activity was examined. Results generally confirm the superiority of the first born over the second born on cognitive activity. Directional trends suggest that the presence of a male sibling enhances quantitative scores, the presence of a female enhances language scores, males having a greater effect on females than vice versa. ProbleDlThe literature regarding the effects of ordinal position on intellectual activities is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…With female subjects there were five such correlations, with males only two. But again, this is consistent with earlier studies in Downloaded by [University of Iowa Libraries] at 04:05 15 March 2015 32 JOURNAL OF GENETIC PSYCHOLOGY which we have shown that females are more affected by other family members than are males (3,4). This result and the above one seem to imply that males are more affected by sex-role standards outside the home than are females.…”
Section: Discussionsupporting
confidence: 93%
“…With female subjects there were five such correlations, with males only two. But again, this is consistent with earlier studies in Downloaded by [University of Iowa Libraries] at 04:05 15 March 2015 32 JOURNAL OF GENETIC PSYCHOLOGY which we have shown that females are more affected by other family members than are males (3,4). This result and the above one seem to imply that males are more affected by sex-role standards outside the home than are females.…”
Section: Discussionsupporting
confidence: 93%
“…A N+ All ( 1964), Hinshelwood ( 1968), Jacoby ( 1968). Jamieson ( 1969), Rosenberg and Sutton-Smith (1964), Schachter (1959), Siegelman (1966), Singer (1964), Stotland et al (1962,1963), Staples and Walters (1961), Weller (1962), Weiss (1966), Wrightsman (1960) and Zuckerman and Link (1968) ; reviews are available in Altus (1966), Burton (1968), Sampson (1965) and Warren (1966). Cross-cultural studies have been reported by Diab and Prothro (1968) and Greene and Clarke (1968).…”
Section: N-mentioning
confidence: 99%
“…It was hypothesized that closely-spaced siblings experience environmental influences similar to those of twins. A number of previous investigations have indicated that sex of sibling is important as well but with no consistent direction in findings (e.g., Chittenden, Foan, Zweil, & Smith, 1968;Cicirelli, 19^7;Koch, 195^, 1956;Rosenberg & Sutton-Smith, 1964). The first sample consisted of a random selection of the 1962 participants and was termed the Normative Sample.…”
Section: Educational Testing Servicementioning
confidence: 92%